The development of phosphinoamine–Pd(II)–imidazole complexes: implications in room‐temperature Suzuki–Miyauracross‐coupling reaction. (24th September 2013) - Borah, Geetika; Boruah, Devajani; Sarmah, Gayatri; Bharadwaj, Saitanya K.; Bora, Utpal
<x xml:space="preserve">Abstract</x> The reaction of N‐methylimidazole (N‐MeIm) and N‐butylimidazole (N‐BuIm) with the complexes [PdCl2(PPh2py–P, N)] and [PdCl2(PPh2Etpy–P, N)] in the presence of NH4PF6 under N2 at room temperature afforded four new cationic Pd(II) complexes [PdCl(PPh2py–P, N)(N‐MeIm)](PF6) (1), [PdCl(PPh2py–P, N)(N‐BuIm)](PF6) (2), [PdCl(PPh2Etpy–P, N)(N‐MeIm)](PF6) (4) and [PdCl(PPh2Etpy‐P, N)(N‐BuIm)](PF6) (5) in good yields, where PPh2py is 2‐(diphenylphosphino)pyridine and PPh2Etpy is 2‐{2‐(diphenylphosphino)ethyl}pyridine). The complexes were fully characterized. The catalytic activities of these complexes were investigated for Suzuki–Miyaura cross‐coupling reactions at room temperature. Complex 2 exhibited excellent activity compared to other analogs. Copyright © 2013 John Wiley & Sons, Ltd.